On the question of determining the location of a short circuit on a power transmission line - N. S. Buryanina; E. V. Lesnykh; A. S. Lesnykh; K. V. Suslov; M. L. Artemyeva (Известия высших учебных заведений: Проблемы энергетики)
An algorithm for eliminating aperiodic components from short circuit (SC) currents is proposed. The algorithm is implemented by computer technology and allows you to determine the location of a short circuit and phase loss in 0.5 - 0.6 milliseconds. During such a time interval, saturation of the magnetic circuits of current transformers (CTs) does not occur, and the processors receive undistorted information from the CTs. To implement the algorithm, four measurements of instantaneous current values, separated by equal time intervals (sampling intervals), are sufficient. Elimination of aperiodic components increases the accuracy of determining the location of the fault. The algorithm can be used to determine the location of phase failure, and in digital relay protection based on measuring currents and voltages.